2014
DOI: 10.1038/ncomms4675
|View full text |Cite
|
Sign up to set email alerts
|

The stimulus-evoked population response in visual cortex of awake monkey is a propagating wave

Abstract: Propagating waves occur in many excitable media and were recently found in neural systems from retina to neocortex. While propagating waves are clearly present under anaesthesia, whether they also appear during awake and conscious states remains unclear. One possibility is that these waves are systematically missed in trial-averaged data, due to variability. Here we present a method for detecting propagating waves in noisy multichannel recordings. Applying this method to single-trial voltage-sensitive dye imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
260
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(287 citation statements)
references
References 68 publications
22
260
5
Order By: Relevance
“…Dominant directionality could be related to the underlying connectivity profile that serves the intra-and intercortical information transfer (57). The computational implication of horizontal connections could point to a preset preferred path for information processing within a given functional domain of the neocortex (60)(61)(62). That such a directional path is "functionally" preserved in sleep could be further evidence that corticothalamic UP states replay fragments of wakefulness (63).…”
Section: Discussionmentioning
confidence: 99%
“…Dominant directionality could be related to the underlying connectivity profile that serves the intra-and intercortical information transfer (57). The computational implication of horizontal connections could point to a preset preferred path for information processing within a given functional domain of the neocortex (60)(61)(62). That such a directional path is "functionally" preserved in sleep could be further evidence that corticothalamic UP states replay fragments of wakefulness (63).…”
Section: Discussionmentioning
confidence: 99%
“…To study spatiotemporal dynamics in these neural recordings, we adapted our previously introduced method for detecting arbitrarily shaped traveling waves (Muller et al, 2014) to multisite ECoG arrays (Figure 1-figure supplements 2 and 3). This approach allowed us to characterize and classify the spatiotemporal dynamics during thousands of episodes of spindling activity in many hours of sleep recordings.…”
Section: Spatiotemporal Dynamicsmentioning
confidence: 99%
“…For the spatial gradient, derivatives are taken across the two dimensions of space and are approximated by the appropriate forward and centered finite differences. As in previous work, phase derivatives were implemented as multiplications in the complex plane (Feldman, 2011;Muller et al, 2014).…”
Section: Spatiotemporal Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, propagation of activity across visual brain areas has been demonstrated previously in MEG (Cottereau et al 2011) and may also contribute to the diversity observed here. A recent study in monkeys even points to the possibility that both scenarios take place in concert, whereby activity travels within different visual areas while maintaining stable phase delays between visual areas (Muller et al 2014).…”
Section: Discussionmentioning
confidence: 99%